2022
DOI: 10.1136/jnis-2022-019160
|View full text |Cite
|
Sign up to set email alerts
|

Natural history, angiographic presentation and outcomes of anterior cranial fossa dural arteriovenous fistulas

Abstract: BackgroundAnterior cranial fossa dural arteriovenous fistulas (ACF-dAVFs) are aggressive vascular lesions. The pattern of venous drainage is the most important determinant of symptoms. Due to the absence of a venous sinus in the anterior cranial fossa, most ACF-dAVFs have some degree of drainage through small cortical veins. We describe the natural history, angiographic presentation and outcomes of the largest cohort of ACF-dAVFs.MethodsThe CONDOR consortium includes data from 12 international centers. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…22 In a retrospective analysis of the Consortium for Dural Arteriovenous Fistula Outcomes Research (CONDOR) database by Sanchez et al, 51 of 60 (85%) patients had CVD, most commonly draining into the superior sagittal sinus (63%, 32/51), followed by the cavernous/petrous sinuses (8%, 4/51). 30 These findings in the literature are supported by our meta-analysis, with 86% of the patients in our review having bilateral ethmoidal arterial supply and 98% having CVD.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…22 In a retrospective analysis of the Consortium for Dural Arteriovenous Fistula Outcomes Research (CONDOR) database by Sanchez et al, 51 of 60 (85%) patients had CVD, most commonly draining into the superior sagittal sinus (63%, 32/51), followed by the cavernous/petrous sinuses (8%, 4/51). 30 These findings in the literature are supported by our meta-analysis, with 86% of the patients in our review having bilateral ethmoidal arterial supply and 98% having CVD.…”
Section: Discussionsupporting
confidence: 82%
“…5 In ethmoidal DAVFs treated as part of the CONDOR database, it was similarly demonstrated that microsurgery (66%, 35/53) had superior obliteration rates to EVT (32%, 17/53). 30 Furthermore, a lower complication rate with microsurgery (6%, 2/35) versus EVT (12%, 2/17) was supported by the CONDOR cohort. 30 These data were substantiated by our current meta-analysis, which showed that surgery had a higher complete obliteration rate (89% vs 70%) and a slightly lower complication rate (10% vs 13%) than EVT.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this case, the patient developed an ACF-dAVF within three days of the initial encounter, which is to our knowledge the first case report of a patient presenting with this condition within one month of the initial injury. In ACF-dAVFs, the cribriform plate is commonly the fistula point, in which afferent arterial supply arises from the distal ophthalmic artery and both anterior and posterior ethmoidal arteries, and venous drainage occurs through frontal cortical veins into the superior frontal sinus or posteriorly into the cavernous sinus or basal vein of Rosenthal [ 14 , 15 ]. In the absence of a more robust dural sinus in the ACF, the fragile pial cortical veinous drainage predisposes ACF-dAVFs for rupture and intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…High-pressure arterial reflux into cortical veins can lead to intracranial hemorrhage, the most dreaded complication of dAVFs. 1 Chronic venous hypertension can also lead to a spectrum of nonhemorrhagic neurological deficits (NHNDs). [2][3][4] Cognitive impairment mimicking a dementing process is a NHND that can be triggered by venous hypertension.…”
mentioning
confidence: 99%